Elliptically symmetric Bessel distribution: the distribution of $XY$ - Nadarajah, Saralees; Gupta, Arjun K. (Tamkang Journal of Mathematics, 2006)
The exact distribution of the product $XY$ is derived when $(X, Y)$ has the elliptically symmetric Bessel distribution.